Oxi-inflammatory stress and vascular cell adhesion molecule-1 in post-COVID active rheumatoid arthritis patients - Siddiqui, Merajul Haque; Agarwal, Jugal Kishor; Agrawal, Dipty; Rahul Saxena,; Ranjan, Rajni; Tyagi, Bhumesh (Asian Journal of Medical Sciences, 2022)
Background: Coronavirus disease-19 (COVID-19) has sparked the deterioration of human health at an unprecedented scale globally and affected the patient’s musculoskeletal health also. It is conceivable that active rheumatoid arthritis (ARA) patients recovered from COVID-19 after second wave are at enhanced risk of cardiovascular complications. Aim and Objectives: In this context, the present study was intended to estimate the soluble vascular cell adhesion molecule-1 (sVCAM-1), serum paraoxonase (PON), and markers of oxi-inflammatory stress in ARA patients diagnosed reverse transcriptase-polymerase chain reaction negative after second wave of COVID-19 and to determine their role in predicting cardiovascular disease (CVD) risk. Materials and Methods: Sixty ARA patients (30–45 years) of Delhi-NCR region were recruited and categorized into two groups (n=30 in each group; on the basis of their history of COVID infection). Using standard methods, study group parameters were estimated in ARA patients and statistically compared it with that of 30 healthy controls by using student’s t-test. Results: Serum sVCAM-1, malondialdehyde (MDA), and C-reactive protein (CRP) levels were significantly high (P<0.001) in Group II and Group III subjects as compared to healthy controls. Conversely, serum PON activity was found to be significantly low (P<0.001) in Group III as compared healthy controls. However, PON activity was altered insignificantly (P<0.1) with respect to Group II subjects. sVCAM-1 levels were positively correlated with MDA, CRP, and atherogenic index; and negatively correlated with PON activity (P<0.001) in post-COVID ARA patients. Conclusion: Thus, enhanced sVCAM-1 and reduced PON activity along with enhanced oxi-inflammatory stress status are more efficient molecular signatures of CVD risk among post-COVID ARA patients. Therefore, the present study emphasizes the dire need of special attention to provide cardiovascular rehabilitation strategy among post-COVID ARA patients along with reduction of oxi-inflammatory stress to reduce the CVD mortality in ARA population.